Expression analysis of the IL-23/Th17 pathway in children with rhinovirus infection - Shu Teng; Mengfei Yu; Zhenghong Qi; Shiyong Zhao; Huaping Wang (Italian Journal of Pediatrics)
Abstract Background The inflammatory response is critical in Human Rhinovirus (HRV) infection-related acute asthma attacks, but its biological mechanisms remain unclear. The interleukin-23 (IL-23)/T helper 17 (Th17) pathway is a key inflammatory pathway that regulates abnormal inflammatory responses. Therefore, this study aims to investigate the role of the IL-23/Th17 pathway in the pathogenesis of wheezing in children with HRV infection by examining the expression of signaling molecules within this pathway. Method Seventy-five pediatric patients hospitalized with HRV infection and 21 healthy children (as a control group) were randomly enrolled from Hangzhou Children’s Hospital between July 2022 and November 2023. HRV-infected patients were stratified into wheezing (n = 42) and non-wheezing (n = 33) groups based on wheezing symptoms. Nasopharyngeal swabs and peripheral venous blood samples were collected on admission. An additional set of peripheral venous blood samples was collected from 22 children in the wheezing group during their recovery phase (day 7 after symptom onset). Th17 cell percentages in peripheral blood lymphocytes were determined using flow cytometry. ELISA was utilized to measure the serum levels of IL-23 and IL-17 and the expression of IL-23R, JAK2, p-JAK2, STAT3, and p-STAT3 in peripheral blood mononuclear cells. Comparisons of expression levels were made among the wheezing, non-wheezing, and control groups, as well as between the acute and recovery phases in the wheezing group. Results Children with wheezing due to HRV infection exhibited significantly higher levels of IL-23 and IL-17 compared to the non-wheezing and control groups (p < 0.05). No significant differences were observed in the expression of other molecules in the IL-23/Th17 pathway across the groups (p > 0.05). During the recovery phase, the levels of IL-23 and IL-17 significantly decreased compared to the acute phase (p < 0.05). Conclusion IL-23 and IL-17 significantly contribute to the development of HRV-associated wheezing in children. However, the IL-23/Th17 pathway may not be the primary mechanism behind HRV-related wheezing illnesses.